Comparison between smart and traditional building materials to achieve sustainability - Mohson, Zainab Hamid; Ismael, Zeyad Ali; Shalal, Saba Salih (Periodicals of Engineering and Natural Sciences (PEN), 2021)
Building materials have been leading architecture since its inception and with the development of building materials throughout history,  gives architecture a broader scope for development, whether at the level of plans, facades or sections .From the first dwelling created by man to contemporary architecture, where the building is the true embodiment of building materials, and traditional building materials based on bricks, wood and iron have developed greatly in terms of appearance and efficiency of use in contemporary architecture, Man seeks when using building materials to reduce the amount of materials used and with the highest functional, structural and aesthetic efficiency, in order to invest them in an optimal manner, leading to the sustainability of building materials. Therefore, the research problem was (The need to know the difference between the sustainability of traditional and contemporary building materials in architecture) The research determined the hypothesis (there is a disparity between the sustainability of traditional and contemporary building materials in architecture) To reach the main objective (studying the sustainability of traditional and contemporary building materials and the construction capabilities of each). This will be done through the study of traditional building materials and contemporary and sustainability of each of them down to a comparison between them in terms of sustainability through the analysis of some architectural examples.